LEARNING QUR’AN WITH FUN GAMES UNTUK MENINGKATKAN MINAT SISWA PADA MATERI AL-QUR’AN - Mia Fitriani (Asaatidzah, 2022)
The Qur'an is the word of Allah which is a guidance for Muslims life, so every Muslim must have special attention to understand it thoroughly. Learning the Qur'an is carried out continuously, from young to old, especially at school. This study aims to increase student's interest and motivation in the process of learning the Koran at SMPN 2 Tirtamulya, Karawang by creating a fun learning atmosphere through Fun Games. This is motivated by the large number of students at SMPN 2 Tirtamulya who have not been able to read and understand the Al-Qur'an properly. This phenomenon is caused by several factors, among the main factors are learning methods that are still conventional and the negative influence of gadgets that make students forget the time and lazy to recite. This study used a qualitative approach with a classroom action research method involving grade 7th (seventh) students and 1 (one) teacher of Islamic Religious Education (PAI) at SMPN 2 Tirtamulya, Karawang. The results of this study indicate that there is a significant change in interest and motivation as well as an increase in the ability of SMPN 2 Tirtamulya students towards Al-Qur'an material, especially in understanding makhrojul letters, tajwid, and their meanings.